2012
DOI: 10.1002/nme.4356
|View full text |Cite
|
Sign up to set email alerts
|

Cohesive zone representation and junction partitioning for crystal plasticity analyses

Abstract: SUMMARY A novel scheme is presented for incorporating finite thickness cohesive interfaces in virtual grain structures for crystal plasticity finite element (CPFE) analyses of intergranular crack initiation and propagation. A Voronoi tessellation model is used to define the virtual grain structure, with automatically generated nonzero thickness cohesive zones (CZs) representing the grain boundaries and multiple junctions. An efficient grain boundary offsetting algorithm is presented, and issues related to auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In recent years, the creep-fatigue damage mechanisms [ 11 , 12 , 13 ] and modeling approaches [ 14 , 15 , 16 , 17 ] have been extensively investigated. For instance, Danilov et al [ 18 ] studied the evolution of the plastic strain macro-localization pattern in low-temperature creep of commercial purity aluminum, and they found that the velocity of plastic strain localization waves is governed by thermally activated dislocation movement.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the creep-fatigue damage mechanisms [ 11 , 12 , 13 ] and modeling approaches [ 14 , 15 , 16 , 17 ] have been extensively investigated. For instance, Danilov et al [ 18 ] studied the evolution of the plastic strain macro-localization pattern in low-temperature creep of commercial purity aluminum, and they found that the velocity of plastic strain localization waves is governed by thermally activated dislocation movement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, crack initiation and propagation are rather dominated by local maximal values around grain boundaries or interfaces (see e.g. [3][4][5]). Various metallic alloys, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, the crystal plasticity based finite element method (CPFEM) has been widely used to analyze anisotropic deformation mechanisms in polycrystalline metals [8][9][10]. This method has also been coupled with the cohesive finite element method (CFEM) to address the material fracture behaviors [11][12][13][14]. Currently, most of these models only consider "virtual" idealized microstructures and intergranular fracture along the grain boundaries.…”
Section: Introductionmentioning
confidence: 99%